Analisis Sensitivitas Deterministik Investasi Pengadaan Alat Berat di Perusahaan Pertambangan Batubara dengan Metode NPV - Rizto Salia Zakri; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. One of the biggest financing components in mining companies, especially coal mining, is production costs, while have contribution of> 20% in total mining costs. On the other hand the production process is the main process in mining, becaus this activity will produce commodities. Heavy equipment is a major component in the production process, the selection of heavy equipment is a determining factor in the calculation of production costs. Methods of procurement of heavy equipment are important in the calculation of production costs, in general there are 3 commonly used heavy equipment procurement methods, namely the direct purchase method (cash), the credit method (leasing), and the rental method. Each method requires a different investment value from each other. In the principle of investment, which is considered as a profitable investment is an investment that provides the greatest returns, it can be in the form of the net present value (NPV) and the largest interest rate ratio (IRR) which is greater than the bank interest rate. Changing commodity values, and rising and falling fuel prices, will affect the investment value of the heavy equipment procurement process, sensitivity analysis is important to know in which conditions the investment is still profitable. Based on the deterministic sensitivity analysis, it can be seen that commodity prices are the most influential parameter on investment returns, while fuel prices do not significantly affect investment returns. The procurement method used is also not affected by changes in investment parameters, the method of procurement of cash is the best option, with a large initial investment value.Keywords: Deterministic Sensivity Analysis, Net Preset Value (NPV), Heavy Equipment, Investment, Coal Mining, Spider Web